Strategie nauki czytania w terapii dzieci z zaburzeniami komunikacji językowej - Bielenda-Mazur, Ewa; Orłowska-Popek, Zdzisława (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
In this article, the authors present the reading difficulties of children with language communication disorders. The authors’ experience in therapy allows them to determine the most important difficulties characteristic of people with particular disorders (SLI, dyslexia, autism, Asperger’s syndrome and deafness) and to propose a strategy for therapy.